Cardiac sarcoidosis: diagnosis and management - Aftab, Abdullah; Szeto, Stanley; Aftab, Zoha; Bokhari, Sabahat (Frontiers in Cardiovascular Medicine, 2024)
Non-caseating granulomatous infiltration of the myocardium is the hallmark of cardiac sarcoidosis (CS). CS manifests clinically as conduction disturbance, ventricular arrhythmia, sudden cardiac death and/or heart failure with reduced ejection fraction. Other than confirmation through endomyocardial biopsy, a diagnosis of probable CS can be established by histological evidence of systemic sarcoidosis in addition to characteristic clinical or advanced imaging findings. Cardiac Magnetic Resonance imaging (CMR) and 18 F-flurodeoxyglycose positron emission tomography (FDG-PET) are imaging modalities indispensable in the diagnosis and monitoring of CS. FDG-PET is the method of choice for identifying the active inflammatory phase of CS and in the monitoring and modifying of immunosuppressive treatment. CMR is better suited for assessing cardiac morphology and function. Both modalities are more effective in detecting CS when used in combination than either is alone. Management of CS is primarily based upon observational data of low quality due to a paucity of randomized controlled trials. Corticosteroid therapy and/or tiered-immunosuppression are the mainstays of treatment in reducing myocardial inflammation. Steroid-sparing agents aim to limit the unfavorable side-effects of a significant steroid burden. Antiarrhythmics and guideline-directed medical therapies are utilized for control of ventricular arrhythmia and left ventricular dysfunction respectively. CS necessitates multidisciplinary care in specialized centers to most effectively diagnose and manage the disease. Additional randomized trials are warranted to further our understanding of medical optimization in CS.